Google : how Google works - Eric Schmidt and Jonathan Rosenberg, with Alan Eagle (John Murray, 2014)
Both Eric Schmidt and Jonathan Rosenberg came to Google as seasoned Silicon Valley business executives, but over the course of a decade they came to see the wisdom in Coach John Wooden's observation that 'it's what you learn after you know it all that counts'. As they helped grow Google from a young start-up to a global icon, they relearned everything they knew about management. How Google Works is the sum of those experiences distilled into a fun, easy-to-read primer on corporate culture, strategy, talent, decision-making, communication, innovation, and dealing with disruption. The authors explain how the confluence of three seismic changes - the internet, mobile, and cloud computing - has shifted the balance of power from companies to consumers. The companies that will thrive in this ever-changing landscape will be the ones that create superior products and attract a new breed of multifaceted employees whom the authors dub 'smart creatives'.
Keywords: Google (Firm)--Management. Internet industry--Management--United States. BUSINESS & ECONOMICS / Leadership